Drug Utilization Study in the Neonatal Intensive Care Unit at Zawia Medical Center, Zawia, Libya - Naema Alouzi; Fathia Murabet; Mufida Yamane (AlQalam Journal of Medical and Applied Sciences, 2026)
Drug utilization research was critical in assessing medication prescribing, use, and management. This was particularly important in neonatal intensive care units, where evidence from clinical trials was limited, and treatment decisions relied heavily on real-world practice. This study aimed to analyze drug utilization patterns and evaluate prescribing practices using the WHO core indicators. A cross-sectional, observational, and retrospective study was conducted in the Neonatal Intensive Care Unit, Zawia, Libya, from September to December 2023. Data from neonates who received at least one medication were collected, including demographic characteristics, clinical outcomes, and prescribed drugs. Medications were categorized using the World Health Organization Anatomical Therapeutic Chemical classification, and prescribing practices were evaluated using World Health Organization core indicators. Of the 372 neonates admitted, 167 met the inclusion criteria. The mean length of stay was 7.52 days, with a discharge rate of 55.7% and a mortality rate of 17.4%. Neonatal sepsis (71.2%) and respiratory distress syndrome (50.3%) were the most prevalent conditions. A total of 853 medications were prescribed, with anti-infective agents accounting for 68.2%. Gentamicin (98.2%) and ampicillin (96.4%) were the most frequently used medications. The average number of drugs per neonate was 5.1, and 96.8% of prescribed drugs were listed in the Libyan Essential Medicines List. The findings emphasized the importance of effective antibiotic stewardship and strengthened infection control to prevent neonatal complications. Strategies such as the active participation of clinical pharmacists and the implementation of therapeutic drug monitoring were recommended to optimize medication use, enhance medication safety, and improve treatment outcomes in neonatal intensive care units.